Watching Wildlife - Chris, Cynthia, 1961- (Book collections on Project MUSE., 2006)
It has never been easier for Americans to observe wild and exotic animals from the comfort and safety of their couches. Several cable channels-Animal Planet, the Discovery Channel, the National Geographic-provide around-the-clock wildlife programming while the traditional networks regularly broadcast animal documentaries, late-night appearances by zoologists and their animal charges, and sensationalistic specials about animals attacking hapless humans. Though the ubiquity of animals on television is new, the genre of the wildlife documentary is as old as cinema itself. In Watching Wildlife, Cy.